The "friend-foe" opposition in Ukrainian linguoculture - Semashko, Tеtіana; Kravets, Larysa; Bondarenko, Alla (Linguistics and Culture Review, 2021)
The friend – foe dichotomy, as a special way of categorising reality, is at the heart of ethnic self-consciousness, building the world around a person. The interpretation "friend" and "foe" is invariably axiological. "Friend" refers to a personal possessor, a socio-cultural group that is identified based on various types of similarity, where "correct", "native", "close", "safe" is perceived as positive. The conceptual model "foe" is the opposition: everything "other", "strange", "unusual", "wrong" is perceived negative. The axiologiness of this opposition is relative and depends on the ethical attitudes of an ethnic group based on the conceptualisation of the friend – foe dichotomy from the standpoint of the binary opposition I – Other; the factors, mechanisms, and results of interaction between the components of the opposition are clarified; the content transformations of the friend – foe dichotomy are traced; the identification function of the latter is updated in the context of modernity. For Ukraine, where the identity development has happened to be incredibly complicated by the incongruity of value, foreign, and political orientations, the issue of borderline, "border strategies", the presence of the "friend" / "foe" dichotomy in the socio-cultural space is extremely relevant.